Characterization and analysis of forest fragments and land use in the municipality of Colares, northeastern Pará, Brazil - Braga, Thaís Gleice Martins; da Silva, Gabriel Máximo; Lima, Madson Oliveira; Silva, Andréa Laize Pureza; Costa, Merilene do Socorro Silva; Pinheiro, Paula Fernanda Viegas; Ferreira, Oberdan Oliveira (Boletim do Museu Paraense Emílio Goeldi - Ciências Naturais, 2018)
This study aimed to analyze the vegetation coverage and land use, as well as the characterization and analysis of forest fragments in Colares municipality in Pará state, Brazil, through products and techniques of remote sensing and improving knowledge of landscape structure, in order to offer subsidies to the planning of territorial occupation. Digital images were used from the Operational Land Imager (OLI)/Landsat 8, orbit/point 223/061, bands 4, 5 and 6, which were processed and classified using the maximum likelihood algorithm. The analyzes related to the configuration of the landscape and natural vegetation fragments were performed using metric classes, using ArcGis software, on Patch Analysis module. The use of remote sensing and geoprocessing allowed us to characterize and analyze the elements that compose the landscape of Colares, showing a mosaic of vegetation cover and land use, high forest fragmentation, identified by the presence of a large number of small fragments, demonstrating the strong impact of human activity in the area. The results also showed the presence of some intact forest fragments, which are important for biodiversity conservation, fulfilling an important role in maintaining local biodiversity.
Keywords: Vegetation coverage; Land use; Metric classes